UTILITY OF SCORE MACAS IN PREGNANT WOMEN WITH COVID 19 ———————————————————————————————————- - Quezada, Jose (InterAmerican Journal of Medicine and Health, 2020)
Maternal morbidity and mortality has been identified by the World Health Organization as one of the main public health problems worldwide today. In previous works, a new Score was developed with parameters that were adjusted to the reality of our pregnant population, which has been called Score Macas, including Serum Lactate as one of the parameters since it has proven to be useful as a predictor of severity of obstetric complications, especially in bleeding and sepsis. We highlight that in the face of the current pandemic that we are experiencing due to COVID 19, several management protocols have been put on the table since it is necessary to determine the best way to reach their diagnosis and classify patients according to their severity and need for intensive care. We propose the application of Score Macas for its availability and adaptation to our situation. It is important to mention that the majority of patients with COVID 19 present a mild disease but approximately 20% evolve into severe forms. Complications in a pregnant woman should be identified and treated early and the presence of comorbidities should be considered. Retrospectively calculating the Macas Score with data from 9 patients diagnosed with COVID 19, in April 2020, it was found that 100% of the patients admitted to the Intensive Care Unit had a score of 3 or more at the expense of the Respiratory Rate, Oxygen Saturation and Serum Lactate; while all the patients who did not enter the ICU presented less than 3 points. We propose the application of this Score in the initial evaluation of patients with pregnancy plus COVID 19.